Benzylsulfonic acid functionalized mesoporous Zr-TMS catalysts: an efficient and recyclable catalyst for the preparation of coumarin derivatives by pechmann condensation reaction - Selvakumar, S.; Chidambaram, M.; Singh, A. P. (Catalysis Communications, 2007)
Benzylsulfonic acid functionalized mesoporous Zr-TMS (Zr-TMS-BSA, Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalyst is used as an alternative to conventional acid catalysts in the von Pechmann condensation of aromatic alcohols with ethyl acetoacetate leading to the formation of coumarin derivatives in solvent free condition at 150 degrees C. Three types of coumarins, 7-hydroxy-4-methylcoumarin (beta-methylumbelliferone), 7-methoxy-4-methylcoumarin (Methyl-4-methylumbelliferyl ether) and 7,8-benzo-4-methylcoumarin derivatives have been prepared using resorcinol, 3-methoxyphenol and 1-naphthol, respectively. The catalytic activity and the recycle studies of the catalyst in all the three reactions proved the superior performance of the catalyst. Further the products were confirmed by GC, elemental analysis, melting point and NMR techniques. Finally, the probable mechanism for Pechmarm condensation using Zr-TMS-BSA catalyst has been reported. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzylsulfonic acid; Pechmann condensation and coumarins; Zr-TMS-BSA catalysts

Benzoylation of anisole over silicotungstic acid modified mesoporous alumina - Selvakumar, S.; Singh, A. P. (Catalysis Letters, 2009)
Mesoporous alumina (MA) molecular sieves were synthesized by using aluminum sec-butoxide as Al precursor and lauric acid as the structure directing agent. The synthesized MA was functionalized with silicotungstic acid (STA) via wet impregnation method and characterized by various physico-chemical techniques. The XRD patterns of a series of HPA functionalized MA are showing the ordered structures. N(2) sorption analysis shows type IV isotherm. NH(3)-TPD measurements revealed an increase in number of acid sites with an increase in loading of STA over MA. At the same time decrease in the acidity was observed with the increase in calcination temperature of the supported materials. Functionalization of STA were also carried out over different alumina supports such as catapol-B (CB) and alumina synthesized without surfactant (ASW) and their activities were evaluated by carrying out liquid phase Friedel-Craft acylation (FC) reaction of anisole with p-toluoyl chloride in a batch reactor at 120 degrees C. Recycling was performed in the FC reaction using 30 wt% STA-MA two times and no major deactivation of the catalyst was observed.
Keywords: Friedel-Craft acylation; Mesoporous alumina; Silicotungstic acid

Nature of the acid sites in the metal triflates immobilized in SBA-15 and their role in the friedel-crafts acylation of naphthalene - Selvakumar, S.; Gupta, Narendra M.; Singh, A. P. (Applied Catalysis A-General, 2010)
The Zn-triflate molecules loaded (5-30 mol%) in mesoporous SBA-15 silicate exhibited considerably higher catalytic activity for liquid-phase Friedel-Crafts (FC) acylation of naphthalene with p-toluoyl chloride, as compared to the corresponding triflates of La, Ce and Y. In situ FTIR studies revealed that the triflate molecules occluded in the channels of SBA-15 may cause severe perturbation of surface hydroxyl groups, without undergoing an electronic binding. The metal cations of the triflate molecules, on the other hand, participated in direct bonding of the reactant molecules and also helped in the formation of some Bronsted type surface acid sites. This article discusses the role of the acid sites generated on occlusion of metal triflates in SBA-15, as monitored by using NH(3)-TPD and pyridine-IR spectroscopy, in the Friedel-Crafts acylation of naphthalene. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acylation; Mesoporous silica; Metal triflate; Naphthalene

Vice to virtue: intracellular biogenic nanoparticles for the generation of carbon supported catalysts - Vijayakumar, P. S.; Selvakumar, S.; Gholap, Ramkrishna S.; Singh, A. P.; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2010)
Intracellular biogenic nanoparticles are considered disadvantageous as the separation of the nanoparticles from the biomass becomes intricate. However realizing the importance of carbon supported catalyst for many important organic reactions we envisaged these nanoparticles as a source for carbon supported catalyst. Herein we demonstrate the heat treatment of intracellular biogenic nanoparticles under inert atmosphere as an efficient method for the preparation of carbon supported metal oxide catalysts. Aspergillus ochraceus, a fungus isolated from foundries, on incubation with K(2)TiF(6) led to the synthesis of intracellular titanium oxide nanoparticles. The nanoparticles embedded biomass upon heat treatment at 600 degrees C in a nitrogen environment gave titanium oxide nanoparticles implanted in a carbonaceous matrix. The material thus formed was characterized using FTIR spectroscopy, Raman spectroscopy, HRTEM and X-ray diffraction. Appreciable benzaldehyde selectivity was observed when styrene oxidation was carried out over such immobilized catalysts. The conversion rate was determined to be 76% and the benzaldehyde selectivity was greater than 80%.
Keywords: Benzaldehyde Selectivity; Biosynthesis; Carbon Supported Titania; Nanoparticles; Styrene Oxidation